A Longitudinal Field Investigation of Narcissism and Popularity Over Time: How Agentic and Antagonistic Aspects of Narcissism Shape the Development of Peer Relationships. (April 2020) - Leckelt, Marius; Geukes, Katharina; Küfner, Albrecht C. P.; Niemeyer, Lisa M.; Hutteman, Roos; Osterholz, Sarah; Egloff, Boris; Nestler, Steffen; Back, Mitja D.
Grandiose narcissism has been linked to initial popularity but to later unpopularity in peer groups and laboratory contexts. Do these effects on peer relationships also emerge in larger real-life contexts and what are the underlying behavioral processes (i.e., behavioral expressions, interpersonal perceptions)? Using data from the longitudinal CONNECT field study ( N = 126), we investigated effects of agentic and antagonistic aspects of grandiose narcissism on emerging popularity in a complete peer network. A cohort of psychology first-year students was assessed with a quasiexperimental, experience-sampling methodology involving online surveys, diaries, and behavioral observations. In contrast to previous laboratory research, narcissism was unrelated to popularity at the level of zero-order correlations. However, results indicated that (a) an agentic behavioral pathway fostered popularity across time, and an antagonistic behavioral pathway drove the long-term decline in popularity, and (b) the two pathways were differentially related to agentic (admiration) and antagonistic (rivalry) aspects of narcissism.